2023
DOI: 10.3389/feduc.2023.1154389
|View full text |Cite
|
Sign up to set email alerts
|

Explaining inequalities of homeschooling in Germany during the first COVID-19 lockdown

Abstract: Current studies suggest that the COVID-19 pandemic is worsening existing social inequalities in the field of education worldwide. In this paper, we argue that the pandemic is especially challenging for students from socially disadvantaged and educationally deprived homes, as parental engagement and resources are very important in terms of guiding and supporting students’ learning processes during this school closure period. To examine how well parents were able to help their children with schoolwork during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Parents' working commitments, cultural resources, and financial stability also play significant roles towards their children's achievement. One study by Sari et al (2023), for example, through multivariate data analysis, has shown that, in Germany parents with limited educational attainment were twice as likely to be unable to provide sufficient support compared to highly educated parents.…”
Section: Introductionmentioning
confidence: 99%
“…Parents' working commitments, cultural resources, and financial stability also play significant roles towards their children's achievement. One study by Sari et al (2023), for example, through multivariate data analysis, has shown that, in Germany parents with limited educational attainment were twice as likely to be unable to provide sufficient support compared to highly educated parents.…”
Section: Introductionmentioning
confidence: 99%